Recent Studies in the Focus of Comparative Phraseology - Anna D. Bakina; Tatiana I. Koykova (Вестник Северного (Арктического) федерального университета: Серия «Гуманитарные и социальные науки»)
The reviewed monograph details the results of the latest research in the field of comparative phraseology conducted on the representative phraseological material of a number of languages: Russian, Georgian, Belarusian, Ukrainian, English, German, Swedish, Czech and Tatar. In particular, the typologically relevant characteristics of the description of phraseological units in Germanic languages are identified; a comparative analysis of phraseological units of biblical origin in Russian and Georgian is provided; the national and cultural specificity of phraseological units portraying wedding traditions in several languages is determined; the category of evaluation in Russian and English proverbs with comparative semantics is considered. The presented phraseological studies in a comparative aspect are significant in theoretical and practical terms and will be of interest to specialists in the fields of phraseology, phraseography, comparative linguistics and translation.